Characteristics of Organic Macerals and Their Influence on Hydrocarbon Generation and Storage: A Case Study of Continental Shale of the Yanchang Formation from the Ordos Basin, China. (15th July 2021) - Xiao, Lei; Li, Zhuo; Hou, Yufei; Xu, Liang; Wang, Liwei; Yang, Youdong
Abstract : Organic macerals are the basic components of organic matter and play an important role in determining the hydrocarbon generation capacity of source rock. In this paper, organic geochemical analysis of shale in the Chang 7 member of the Yanchang Formation was carried out to evaluate the availability of source rock. The different organic macerals were effectively identified, and the differences in hydrocarbon generation and pore-forming capacities were discussed from two perspectives: microscopic pore development and macroscopic hydrocarbon generation through field emission scanning electron microscopy (FE-SEM) and energy-dispersive spectrum (EDS) analyses, methane isotherm adsorption, and on-site analysis of gas-bearing properties. The results show that the source rock of the Chang 7 member has a high abundance of organic matter and moderate thermal evolution and that the organic matter type is mainly type I. Based on the morphology of the organic matter and the element and pore development, four types of hydrogen-rich macerals, including sapropelite and exinite, and hydrogen-poor macerals, including vitrinite and inertinite, as well as the submacerals, algae, mineral asphalt matrix, sporophyte, resin, semifusinite, inertodetrinite, provitrinite, euvitrinite, and vitrodetrinite, can be identified through FE-SEM and EDS. A large number of honeycomb-shaped pores develop in sapropelite, and round-elliptical stomata develop in exinite, while vitrinite and inertinite do not develop organic matter pores. The hydrogen-rich maceral is the main component of organic macerals in the Chang 7 member of the Yanchang Formation. The weight percentage of carbon is low, so it has good hydrocarbon generation capacity, and the organic matter pores are developed and contribute 97% of the organic matter porosity, which is conducive to hydrocarbon generation and storage. The amount of hydrogen-poor maceral is low, and the weight percentage of carbon is low, and the organic matter pores are not developed, which is not conducive to hydrocarbon generation and storage.